Mountaineering Stories of Adventurous Women: A Brief Survey - Gautam, Pragya (Research Journal of Padmakanya Multiple Campus, 2023)
This article looks at the dream and the achievement of adventurous women in the field of mountaineering. It focuses on Everest climbing and the narrations of Lhakpa Phuti Sherpa, a Nepalese mountaineer, Rebecca Stephens, the first British Everest climber, and Lene Gammelgaard, the first Scandinavian woman to summit Mount Everest. The magic of Mount Everest, its beauty, mystery, and majesty lures the women's adventurous souls. They are emotionally and spiritually connected to the mountains because the high peaks are the sources of peace, happiness, and enlightenment to them. Mountaineering, the art of climbing mountain peaks, is a perilous sport that attracts climbers from all over the world. Despite the challenges, the climbers risk their lives to thin air, frostbite, bone-chilling temperatures, avalanches, and powerful winds. They understand that getting to the top is not always simple, but it is worthwhile because it represents self-conquest, and touch with greater power. In this article, the three women climbers mention their invincible courage and inexhaustible stamina to ascend the steep and rugged snow peak of Mount Everest.